Emotional contagion as a trigger for moral disengagement: Their effects on workplace injuries. (August 2021) - Petitta, Laura; Probst, Tahira M.; Ghezzi, Valerio; Barbaranelli, Claudio
Highlights: CoVid-19 pandemic generates additional emotional pressure at work and requests in order to work safely. Emotional pressure at work triggers moral justifications for safety violations. Moral disengagement mechanisms may increase the experience of work-related injuries. Organizations should develop an emotional ecosystem that may lead to enhance employee loyalty and compliance to rules. Abstract: The purpose of this study was to empirically test the proposition that contagion of emotions triggers moral disengagement and subsequent increases in work-related injuries. Using emotional contagion and social cognitive theories, we tested the proposition that higher contagion of anger (i.e., a negative emotion that interferes with mental functioning and enables inappropriate behavior) would trigger moral justifications for safety violations, whereas higher contagion of joy (i.e., a positive emotion accompanied by an optimal operating condition and constructive activity) would prevent safety-related moral disengagement. In turn, moral disengagement was predicted to be related to higher rates of subsequent workplace injuries. Using a cross-country and multi-method (i.e., cross-lagged, cross-sectional) design, data from 503 employees in the U.S. (two-wave) and 538 employees in Italy (cross-sectional) supported the hypothesized mediation model. Specifically, both in the U.S. and Italy, emotional contagion of anger positively predicted moral disengagement, whereas emotional contagion of joy negatively predicted moral disengagement. Furthermore, moral disengagement positively predicted experienced injuries and partially mediated the relationship between contagion of joy/anger and injuries. These findings suggest that moral justifications of safety violations, and related injuries, may be prevented by exchanges of positive emotions (and triggered by exchanges of negative emotions) that employees absorb during social interactions at work. Theoretical and practical implications for organizational ethics are discussed in light of the globally increasing emotional pressure and concerns for a safe and psychologically healthy environment in today's workplace, particularly given the recent pandemic spread of Coronavirus disease (CoVid-19).